New WHO recommendations on preoperative measures for surgical site infection prevention: an evidence-based global perspective. Issue 12 (December 2016) - Allegranzi, Benedetta; Bischoff, Peter; de Jonge, Stijn; Kubilay, N Zeynep; Zayed, Bassim; Gomes, Stacey M; Abbas, Mohamed; Atema, Jasper J; Gans, Sarah; van Rijen, Miranda; Boermeester, Marja A; Egger, Matthias; et al.
Summary: Surgical site infections (SSIs) are among the most preventable health-care-associated infections and are a substantial burden to health-care systems and service payers worldwide in terms of patient morbidity, mortality, and additional costs. SSI prevention is complex and requires the integration of a range of measures before, during, and after surgery. No international guidelines are available and inconsistencies in the interpretation of evidence and recommendations of national guidelines have been identified. Given the burden of SSIs worldwide, the numerous gaps in evidence-based guidance, and the need for standardisation and a global approach, WHO decided to prioritise the development of evidence-based recommendations for the prevention of SSIs. The guidelines take into account the balance between benefits and harms, the evidence quality, cost and resource use implications, and patient values and preferences. On the basis of systematic literature reviews and expert consensus, we present 13 recommendations on preoperative preventive measures.